INTEGRASI KEUNGGULAN PENDIDIKAN DAN STRATEGI PEMASARAN 7P DALAM MEMBANGUN BRANDING SEKOLAH ISLAM STUDI KASUS SDIT AT-TAUBAH BATAM - Asrulla; Yumesri; Firdaus Jeka; Farida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines branding management at At-Taubah Integrated Islamic Elementary School in Batam through the 7P Marketing Mix framework, including Product, Price, Place, Promotion, People, Process, and Physical Evidence. A descriptive qualitative approach was employed using in-depth interviews, observation, and documentation, involving the school principal, educators, students, and parents. The findings reveal that school branding is a strategic and integrated process supported by flagship programs, credible leadership, high-quality educational services, and the internalization of Islamic values. Flagship programs such as Qur’an memorization (Tahfiz Al-Qur’an), Islamic character education, digital learning, and bilingual instruction serve as key differentiators in strengthening institutional identity. This branding management significantly contributes to enhancing reputation, competitiveness, and public trust.